Comparison Between the Polymerase Chain Reaction-Based Screening and the Southern Blot Methods for Identification of Fragile X Syndrome - Carvalho Curtis-Cioffi, Karen M.; Rodrigueiro, Debora Aparecida; Rodrigues, Valter Curi; Barretto Cicarelli, Regina M. [UNESP]; Scarel-Caminaga, Raquel Mantuaneli [UNESP] (Mary Ann Liebert, Inc., 2012)
The fragile X syndrome (FXS), the most common cause of hereditary mental retardation, is caused by expansions of CGG repeats in the FMR1 gene. The gold-standard method to diagnose FXS is the Southern blot (SB). Because SB is laborious and costly, some adaptations in the polymerase chain reaction (PCR) method have been utilized for FXS screening. A previous PCR-based screening method for FXS identification utilizing small amounts of DNA was reported as simple and efficient. The aim of this study was to reproduce the mentioned PCR-based screening method for identification of expanded alleles of the FMR1 gene in Brazilian individuals and to investigate the efficiency of this method in comparison with SB. Utilizing the enzyme Expand Long Template PCR System, 78 individuals were investigated by that PCR-based screening method for FXS identification. Conclusive results were obtained for 75 samples. Considering all the allelic forms of FXS (normal [NL], premutation [PM], and full-mutation [FM]), the comparison of the PCR-based screening method with SB demonstrated 100% of accuracy, sensitivity, and specificity. However, when the PM and the FM were analyzed separately from each other, but together with the NL allele, the accuracy, sensitivity, and specificity decreased (to 42.9%-97.4%). We concluded that the PCR-based screening method was reproducible and capable of identifying all different FXS alleles, but because the differentiation between the PM and the FM alleles was not accurate, SB is still the gold-standard method for the molecular diagnosis of FXS.